2013
DOI: 10.1007/s00259-013-2633-2
|View full text |Cite
|
Sign up to set email alerts
|

Initial clinical results of simultaneous 18F-FDG PET/MRI in comparison to 18F-FDG PET/CT in patients with head and neck cancer

Abstract: PET/MRI of patients with head and neck cancer yielded good diagnostic capability, similar to PET/CT. Further studies on larger cohorts to prove these first results seem justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 17 publications
2
88
1
1
Order By: Relevance
“…One study reported that PET/MRI increased sensitivity for detecting cervical lymph node metastasis over MRI only (89.5 % vs. 65.8 %, respectively) but there was no significant difference with standalone PET (86.8 %) [32]. In another study, diagnostic performance of PET/MRI showed 80.5 % of sensitivity, 88.2 % of specificity, 75.6 % of positive predictive value (PPV), and 92.5 % of negative predictive value (NPV) and those of PET/CT showed 82.7, 87.3, 73.2, and 92.4 %, respectively [33].…”
Section: Head and Neck Cancermentioning
confidence: 96%
“…One study reported that PET/MRI increased sensitivity for detecting cervical lymph node metastasis over MRI only (89.5 % vs. 65.8 %, respectively) but there was no significant difference with standalone PET (86.8 %) [32]. In another study, diagnostic performance of PET/MRI showed 80.5 % of sensitivity, 88.2 % of specificity, 75.6 % of positive predictive value (PPV), and 92.5 % of negative predictive value (NPV) and those of PET/CT showed 82.7, 87.3, 73.2, and 92.4 %, respectively [33].…”
Section: Head and Neck Cancermentioning
confidence: 96%
“…A retrospective analysis of 81 oncologic patients who underwent contrast-enhanced 18 F-FDG PET/CT and subsequent PET/MRI was performed by two readers for incidental tracer uptake. In a consensus reading, discrepancies were resolved.…”
Section: Methodsmentioning
confidence: 99%
“…The examinations were performed on a Biograph mCT TM (Siemens Healthcare GmbH). At the time of 18 F-FDG injection, blood glucose levels were below 150 mg/dL.…”
Section: Pet/ctmentioning
confidence: 99%
See 2 more Smart Citations